2020
DOI: 10.3390/w12102766
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Variation of Dissolvable PAHs in Receiving Water in a Reclaimed Water Irrigation Region

Abstract: Long-term wastewater and reclaimed water irrigation systems constitute the major processes in local water circulation, which concomitantly introduce plenty of undesirable substances that can threaten water quality, ecosystem functions and human health. At the Southeast Reclaimed Water Irrigation Region (SRWIR) of Beijing, wastewater irrigation was adopted from 1969 to 2002, and second-treated effluents (reclaimed water) has been used thereafter. Polycyclic aromatic hydrocarbons (PAHs) were the most ubiquitousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…A significant positive correlation between soil pH H2O /pH KCl and PAHs suggested that the soil’s pH was a key factor in the soil PAHs levels. The statistical negative correlation of all rings PAHs with EC suggest that this factor also indirectly affects the degradation of PAHs in soils 45 . The same results were observed for the application of zeolite composites mixed with leonardite 29 .…”
Section: Discussionmentioning
confidence: 98%
“…A significant positive correlation between soil pH H2O /pH KCl and PAHs suggested that the soil’s pH was a key factor in the soil PAHs levels. The statistical negative correlation of all rings PAHs with EC suggest that this factor also indirectly affects the degradation of PAHs in soils 45 . The same results were observed for the application of zeolite composites mixed with leonardite 29 .…”
Section: Discussionmentioning
confidence: 98%
“…These PAHs' physiochemical and toxic properties raise a significant concern over their impact on soil and groundwater contamination (Wang et al, 2009 ). Moreover, several reports showed evidence of PAH contamination in different soil and groundwater sources (Sushkova et al, 2018 ; Haleyur et al, 2019 ; Lu et al, 2019 ; Liang et al, 2020 ; Pacwa-Płociniczak et al, 2020 ; Picariello et al, 2020 ; Wang Y. et al, 2020 ; Wolf et al, 2020 ; Ambade et al, 2021a , b ; Qiao et al, 2021 ). Therefore, the PAH contamination problem requires more research in this direction using chemical cleavage.…”
Section: Soil and Groundwater Contamination By Pahs And Aromatic Ring Hydroxylating Dioxygenase (Arhd)mentioning
confidence: 99%